The Effect of the Prior Teacher on Value-Added - Gilraine, Michael; McCarthy, Odhrain (The Review of Economics and Statistics, 2026)
We show that teachers’ value added (VA) depends on the VA of the teachers who preceded them. To do so, we use administrative data from North Carolina and find that a one-standard deviation increase in last grade’s mean teacher VA causes a 0.08σ decrease in teacher VA. Controlling for prior teacher assignment eliminates this bias. Under a benchmark policy that releases teachers in the bottom 5% of the VA distribution, 32% of teachers are incorrectly released using traditional techniques. Our results highlight the importance of incorporating dynamic features of education production into the estimation of teacher quality.